Living in the Land of Our Ancestors: Rama Indian and Creole territory in Caribbean Nicaragua / Gerald Riverstone - Riverstone, Gerald (2004)
Nicaraguan and the international context for indigenous land rights, between the forest and the sea, culture, landscape, and livelihood in southeastern Nicaragua, tracing the history of the Rama indians and their lands, Rama and creole territory in the context of the new indigenous land demarcation law, summary amd recommendations.